Propuesta metodológica para la aplicación del modelo Supply Chain Operations Reference - Salazar Sanabria, Hugo Felipe; Lopez Bello, Cesar Amilcar (Ingeniería, 2008)
The SCOR (Supply Chain Operations Reference) model is a strategic management tool aimed to provide a global vision of the entire Supply Chain (SC). The model, in one hand, specifies each of the involved elements and processes; on the other hand it analyzes, measures and establishes performance goals, identifies opportunities for improvement, determines best practices and prioritizes rojects in order to ensure the fulfillment of the promise of service through the distribution system. This paper discusses an SCOR configuration of a basic supply chain, the advantages of using the SCOR model, and the main tools in the management of any SC. It also contains a proposal of a methodology and its application to an organization within the forest industry